Chemically deposited tungsten fibre-reinforced tungsten – The way to a mock-up for divertor applications. (December 2016) - Riesch, J.; Aumann, M.; Coenen, J.W.; Gietl, H.; Holzner, G.; Höschen, T.; Huber, P.; Li, M.; Linsmeier, Ch.; Neu, R.
Highlights: Fabrication of tungsten fibre-reinforced tungsten (Wf /W) for divertor applications by a chemical deposition process. A layered deposition process to produce Wf /W tiles suitable for divertor mock-up applications. Charpy impact tests at room temperature including an estimation of the fracture toughness. Temperature window for Wf /W and investigation of crack growing resistance by FEM modelling. Advanced fabrication methods including textile techniques, a new deposition device and infiltration modelling. Abstract: The development of advanced materials is essential for sophisticated energy systems like a future fusion reactor. Tungsten fibre-reinforced tungsten composites (Wf /W) utilize extrinsic toughening mechanisms and therefore overcome the intrinsic brittleness of tungsten at low temperature and its sensitivity to operational embrittlement. This material has been successfully produced and tested during the last years and the focus is now put on the technological realisation for the use in plasma facing components of fusion devices. In this contribution, we present a way to utilize Wf /W composites for divertor applications by a fabrication route based on the chemical vapour deposition (CVD) of tungsten. Mock-ups based on the ITER typical design can be realized by the implementation of Wf /W tiles. A concept based on a layered deposition approach allows the production of such tiles in the required geometry. One fibre layer after the other is positioned and ingrown into the W-matrix until the final sample size is reached. Charpy impact tests on these samples showed an increased fracture energy mainly due to the ductile deformation of the tungsten fibres. The use of Wf /W could broaden the operation temperature window of tungsten significantly and mitigate problems of deep cracking occurring typically in cyclic high heat flux loading. Textile techniques are utilized to optimise the tungsten wire positioning and process speed of preform production. A new device dedicated to the chemical deposition of W enhances significantly, the available machine time for processing and optimisation. Modelling shows that good deposition results are achievable by the use of a convectional flow and a directed temperature profile in an infiltration process.